In the given figure:
Angle ABD is the sum of Angle ABC and Angle CBD
i.e.
![\angle ABD=\angle ABC+\angle CBD](https://img.qammunity.org/2023/formulas/mathematics/college/p2ldzy2obryl1v6kucutfb7vyr3mcnu0b8.png)
From the given data, we have:
Angle ABD = 70
Angle CBD = 5x + 13
Angle ABC = 3x + 33
Substitute the value and simplify for the x:
![\begin{gathered} \angle ABD=\angle ABC+\angle CBD \\ 70=(3x+33)+(5x+13) \\ 70=3x+33+5x+13 \\ 70=3x=5x+33+13 \\ 70=8x+46 \\ 8x=70-46 \\ 8x=24 \\ x=(24)/(8) \\ x=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1wmiybg33d92fak2x8fsd742plxvwfciym.png)
x = 3
The expression for angle ABC is :
Angle ABC = 3x + 33
Substitute the value of x = 3 in the expression and simplify:
Angle ABC = 3x + 33
Angle ABC = 3(3) + 33
Angle ABC = 9 + 33
Angle ABC = 42°
m
Answer : m